2012
DOI: 10.1371/journal.pone.0042255
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomic Analysis of Noncardia Gastric Cancer from Individuals of Northern Brazil

Abstract: Gastric cancer is the second leading cause of cancer-related death worldwide. The identification of new cancer biomarkers is necessary to reduce the mortality rates through the development of new screening assays and early diagnosis, as well as new target therapies. In this study, we performed a proteomic analysis of noncardia gastric neoplasias of individuals from Northern Brazil. The proteins were analyzed by two-dimensional electrophoresis and mass spectrometry. For the identification of differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 72 publications
2
17
0
1
Order By: Relevance
“…It has been suggested that loss of mitochondrial PHB expression (cytoplasmic localization, as observed in our samples) could lead to accelerated proteolysis of membrane proteins and impair function of the mitochondrial respiratory chain [10]. Our previous proteomic study showed that several proteins involved in energy metabolism pathways (mitochondrial dysfunction, pyruvate metabolism, oxidative phosphorylation, citrate circle, glycolysis/gluconeogenesis) were deregulated [31] and suggested that prominent mitochondrial functions may be altered, shifting energy production in GC cells and suggesting the Warburg effect [32].…”
Section: Discussionsupporting
confidence: 51%
“…It has been suggested that loss of mitochondrial PHB expression (cytoplasmic localization, as observed in our samples) could lead to accelerated proteolysis of membrane proteins and impair function of the mitochondrial respiratory chain [10]. Our previous proteomic study showed that several proteins involved in energy metabolism pathways (mitochondrial dysfunction, pyruvate metabolism, oxidative phosphorylation, citrate circle, glycolysis/gluconeogenesis) were deregulated [31] and suggested that prominent mitochondrial functions may be altered, shifting energy production in GC cells and suggesting the Warburg effect [32].…”
Section: Discussionsupporting
confidence: 51%
“…HSPs are responsible for many cytoprotective mechanisms to stress conditions . HSP27 , HSP60, HSP70 , HSP90, and HSP 105 were observed in previous studies. Other proteins as enolase‐alpha (ENOA), annexin (ANXA) , transgelin (TGLN) , carbon anhydrase 2 (CA2) have been reported in several gastric cancer proteomic studies.…”
Section: Discussionmentioning
confidence: 74%
“…Of the proteins with decreased abundance, some have already been reported to be associated with GA, such as ADH1C , HADH , IDH2 , and IGHG1 . AIFM1 was found decreased in our case, although it has been reported as increased in the literature , as also seen for HADH .…”
Section: Resultsmentioning
confidence: 99%